EVALUASI PROSEDUR PENGELOLAAN DANA BANTUAN OPRASIONAL SEKOLAH (BOS) DALAM MENILAI EFEKTIFITAS DANA PADA SEKOLAH DASAR ISLAM TERPADU (SDIT) BINA AULADI DEPOK - Sri Setiawati (JURNAL LENTERA AKUNTANSI, 2019)
This research , from April 2018 to August 2018, with the title: "Evaluation of School Oprational Aid Fund Management Procedures (BOS) in Assessing Fund Effectiveness in Integrated Islamic Primary Schools (SDIT) Bina Auladi Depok". This study aims to produce information in the form of an explanation of the application and evaluation of the procedures for managing funds and contributing suggestions for schools. The analytical method used in this study is to evaluate the procedures for managing funds in the field compared to library research by collecting books that relate to the effectiveness of funds by interviewing the principal or leadership and financial staff. The results of the study show that the accounting information system is particularly effective in managing funds. This can be seen from the organizational structure that is in accordance with the characteristics of the school, adequate and well-designed documents, internal control systems and adequate reports.Key words: evaluation, management, assistance, operations, school.